At Westonci.ca, we provide reliable answers to your questions from a community of experts. Start exploring today! Join our platform to get reliable answers to your questions from a knowledgeable community of experts. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.

Se the laplace transform to solve the given initial-value problem. y'' − y' = et cos t, y(0) = 0, y'(0) = 0

Sagot :

The solution to this problem is (s2+1)Y(s)−2s−1=2s2+4 .

We let  L[y(t)]=Y(s) . With that, tabular Laplace-transform laws entail

L[y′]=sY(s)−y(0)=sY(s)−2

L[y′′]=s2Y(s)−sy(0)−y′(0)=s2Y(s)−2s−1

∴L[y′′+y]=(s2+1)Y(s)−2s−1 .

Since the Laplace transform of  sin(kt)  is  ks2+k2 , we have

(s2+1)Y(s)−2s−1=2s2+4 .

This equation readily solves to  Y(s)=2s3+s2+8s+6(s2+1)(s2+4) . We compute its partial fraction decomposition as  Y(s)=2s+53s2+1+−23s2+4 .

Our final step is to use tabular Laplace-transform laws ( sin(kt)↦ks2+k2 , and  cos(kt)↦ss2+k2 ) to get  y(t)=2cost+53sint−13sin(2t) . One can check that this indeed satisfies the initial value problem.

For more information about laplace transform, visit

https://brainly.com/question/14701796

#SPJ4

Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. We appreciate your time. Please come back anytime for the latest information and answers to your questions. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.